Export quality management : an answer book for small and medium-sized exporters (ITC GenevaCH, 2001)
Addresses such issues as technical regulations and standards; product certification; testing; metrology; quality management; ISO 900; other management systems; accreditation and the Agreements on Technical Barriers to Trade and Sanitary & Phytosanitary Measures.
Keywords: QUALITY CONTROL